Avaliação do controle postural durante a execução do star excursion balance test - Petter, Gustavo do Nascimento (2017)
The Star Excursion Balance Test (SEBT) is a clinical test that aims to evaluate postural control. The interpretation of its results depends on the understanding of the motor specificities and the compensation mechanisms required in each direction of the test. The objective of this study is to identify biomechanical factors related to the requirements of compensation mechanisms for postural control between the different directions of the SEBT. This study is a cross-sectional, descriptive and correlational research. Its accomplishment happened in the Laboratory of Biomechanics of the Federal University of Santa Maria, in the Center of Physical Education and Sports. Sixteen healthy individuals, aged between 20 and 30 years old, practicing physical activity and without lower limb dysfunctions participated in the study. Measurements were made by performing the SEBT on the force platform and simultaneously the kinematic analysis. The results indicate that the position of the center of pressure (COP) at the touch differs from the anterior direction to the other directions of the SEBT and the performance in this direction is correlated with the proximity of the COP to the anterior limit of the support base. The performances in the other directions did not correlate with the COP position. Also, the anterior direction of the SEBT seems to require a greater extensor moment of the knee and ankle joints than of the hip. The posteromedial direction seems to require a greater extensor moment of the knee joint, followed by the hip. And finally, the posterolateral direction seems to require a greater extensor moment of the hip and knee joints than of the ankle. So, we conclude that the requirements of the compensation mechanisms for postural control are different between the directions of the SEBT.